(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The article discusses the analysis of moving electromagnetic screen motion converters, functional converters, computational converters, compensating converters. Further studies have also shown that devices can be used to analyze hypersensitivity due to their relatively low sensitivity, accuracy of static characteristics, and narrow line area, based on the need to focus on the development of moving screen devices with a wide range of accuracy and static characteristics.